(untitled) (Journal of Partial Differential Equations, 2023)
This paper is concerned with the asymptotic behavior of a quasilinear viscoelastic equation with nonlinear damping and memory. Assuming that the kernel μ (s) satisfies μ'(s)-k_1μ^m(s), 1m